Haemorrhagic septicaemia in cattle and buffaloes: are we ready for freedom? - Saharee, Abdul Aziz (Universiti Putra Malaysia, 2006)
Definition: Haemorrhagic septicaemia (HS) 'penyakit hawar lembu' as it is known in malay, is an acute septicaemic disease caused by the bacteria Pasteurella multocida type B:2 or E. It affects mainly cattle and buffaloes and is characterized by a rapid course, high fever, loud and stertorous breathing due to oedematous swelling, petechial haemorrhages in the throat and brisket region, profuse salivation, severe depression and death within 24 hours. The disease has been described mainly in countries with less developed animal industry in Africa, Asia including Malaysia. (De Alwis MCL, 1999).